Study on bioactive compounds of microalgae as antioxidants in a bibliometric analysis and visualization perspective - Yang, Ning; Zhang, Qingyang; Chen, Jingyun; Wu, Shilin; Chen, Ran; Yao, Liping; Li, Bailei; Liu, Xiaojun; Zhang, Rongqing; Zhang, Zhen (Frontiers in Plant Science, 2023)
Natural antioxidants are more attractive than synthetic chemical oxidants because of their non-toxic and non-harmful properties. Microalgal bioactive components such as carotenoids, polysaccharides, and phenolic compounds are gaining popularity as very effective and long-lasting natural antioxidants. Few articles currently exist that analyze microalgae from a bibliometric and visualization point of view. This study used a bibliometric method based on the Web of Science Core Collection database to analyze antioxidant research on bioactive compounds in microalgae from 1996 to 2022. According to cluster analysis, the most studied areas are the effectiveness, the antioxidant mechanism, and use of bioactive substances in microalgae, such as carotene, astaxanthin, and tocopherols, in the fields of food, cosmetics, and medicine. Using keyword co-occurrence and keyword mutation analysis, future trends are predicted to improve extraction rates and stability by altering the environment of microalgae cultures or mixing extracts with chemicals such as nanoparticles for commercial and industrial applications. These findings can help researchers identify trends and resources to build impactful investigations and expand scientific frontiers.